Influence Of Relocation, Infrastructure, And Islamic Business Ethics On Consumer Decisions In The New Market, Mandailing Natal District With Consumer Behavior As An Intervening Variable - Rizka Nasution; Maryam Batubara; Nur Ahmadi Bi Rahmani (LPPM Universitas PGRI Sumatera Barat, 2024)
The aim of the research is to determine the direct and indirect influence of relocation, infrastructure and Islamic business ethics variables on consumer decisions at Pasar Baru Mandailing Natal Regency with consumer behavior as an intervening variable. This research method uses a quantitative approach with pathways and uses the SPSS version 22 program. This research uses a questionnaire with a sample of 400 respondents. The research results show that relocation partially influences consumer decisions, infrastructure does not partially influence consumer decisions, and Islamic business ethics partially influences consumer decisions. Furthermore, relocation, infrastructure and Islamic business ethics partially influence consumer behavior. From the results of the significance test, it was found that relocation had a significant and real effect on consumer decisions through consumer behavior. And for the infrastructure variable, Islamic business ethics also significantly influences consumer decisions through consumer behavior with a confidence level of 95% or an error rate of 5%.